The battle for talent - Cronsell,Hanna; Lindahl,Lykke (2020)
This thesis is placed in the context of talent management and revolves around the phenomena of talent and talent wars. The two phenomena have received increased attention in the talent management discourse during the last decades as the international competitiveness for talents among organizations has become amplified. The purpose of this thesis has been to explore, analyze and compare different perceptions of talent and experiences of a talent war. The sample population included in house and outsourced professionals involved in recruitment in the Swedish private service sector. This study has adopted a social constructivist perspective and an abductive approach.The empirical data was collected through 16 semi-structured interviews which subsequently were analyzed by the use of a qualitative content analysis in order to detect themes and patterns. The results indicated that talent perceptions are highly individual and there seemed to not be any connections between professional belonging and talent perceptions. However, the diverse ways of defining talent did not indicate that the professionals actively worked with talent diversity. On the contrary, none of the participants responded that they have an organizational talent diversity framework to rely on in the attraction and recruitment of talents. The study found a discrepancy among the professional groups in regards to the existence of a talent war. The outsourced professionals believed that the talent war existed while the in house professionals were less certain. Different experienced factors contributing to a talent war were also discovered.
Keywords: talent; talent management; talent perceptions; war for talent; talent diversity; employee attraction; employee recruitment